Theater as allegory (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
Theater as allegory is a pedagogical system of staging that is in the center of contemporary tendencies of Performing Art Pedagogy. His focus is the relationship of doing and appreciating art. The allegoric figure highlights text and/or images, opening space for imagination and playing to the reader/player or spectator.
Keywords: Pedagogy of Performance; Allegory; Art education